Childfree dalam Pernikahan Kembali Duda dan Janda: Perspektif Kemaslahatan dan Gender - Hermanto, Agus; Bunyamin, Mahmudin; Dharmayani, Dharmayani; Hadaiyatullah, syeh Sarip; Yuhani’ah, Rohmi (JOM, 2025)
This study examines the phenomenon of childfree decisions in remarriage among widows and widowers, particularly within older generations, despite Islam’s emphasis on regeneration through marriage. The research aims to analyze the arguments underlying the choice to remain childfree in remarriage from a gender perspective, focusing on the principle of maslahat (benefit). Employing a qualitative approach with a gender lens, the study utilizes in-depth interviews to collect data from remarried individuals over the age of 50 who have previously been married. The findings reveal that the primary motivations for choosing to remain childfree include having children from previous marriages and prioritizing their upbringing, as well as focusing on career advancement at its peak without the additional responsibility of raising children. From a gender perspective, this choice is perceived as a form of maslahat as it promotes a balanced distribution of responsibilities and partnership within the family. Theoretically, this study contributes to discussions on gender roles in marriage by demonstrating how remarried individuals negotiate parental responsibilities and career aspirations within the framework of maslahat.